Low cost, portable, 3D printable tissue precision slicer - Beatriz Martinez-Martin; Isabella Lambros; Lukas Nuesslein; Yubing Sun (HardwareX)
Slicing tissue samples into thin pieces is commonly used in histology analysis and more recently for organotypic culture when tissue samples are sliced alive. Currently available devices for slicing tissue samples are either designed for fixed tissue samples at low cryogenic temperatures (e.g., Cryostats), or bulky and expensive (e.g., vibratome), preventing them from routine lab usage. Here we report a cost-effective device designed to section live tissues for subsequent culture. This device consists of components crafted from 3D-printed Nylon-12- a material suitable for autoclaving to ensure sterility. Its small footprint enhances portability, allowing for convenient placement within a biosafety cabinet for an added layer of sterility assurance. Using human pluripotent stem cells derived brain organoids as an example, we demonstrated that the device both precisely and accurately makes slices. We further validate its suitability for long-term culture by extended tissue culture following slicing. Our results indicate that brain organoid slices are viable and show improved proliferation rate compared with unsliced organoids.